Effect of heat stress on ileal epithelial barrier integrity in broilers divergently selected for high- and low-water efficiency - Greene, Elizabeth S.; Roach, Brooklee; Cuadrado, Maria Fernandez; Orlowski, Sara; Dridi, Sami (Frontiers in Physiology, 2025)
Water scarcity and rising global temperatures are two of the greatest current and future threats to poultry sustainability. Therefore, selection for water efficiency (WE) and heat resilience are of vital importance. Additionally, intestinal integrity is of critical importance under challenging conditions to maintain nutrient absorption and therefore, growth and performance of broilers. Here, we examined the effect of chronic cyclic heat stress (HS) on the ileal expression profile of tight-junction, gap-junction, adherens, and desmosome genes in the fourth generation of divergently selected low (LWE)- and high water efficient (HWE)-chicken lines. LWE birds exhibited higher levels of gut permeability, regardless of temperature, as measured by fluorescein isothiocyanate–dextran (FITC-D). Among the claudins (CLDN), Cldn1 showed greater expression in the HWE as compared to LWE, regardless of temperature. Cldn5, -16, -20, and -34 genes were all greater in LWE and lower in HWE during HS. Conversely, Cldn25 was decreased in LWE but increased HWE under HS. Cldn4 was increased in the HWE line and decreased by HS. Cingulin (Cgn) gene expression was lower in HWE as compared to LWE and lower in HS as compared to thermoneutral (TN) condition. Gap junction protein α1 (Gja1) and desmoglein 4 (Dsg4) were greater in the HWE as compared to the LWE. Cadherin 1 (Cdh1) gene expression was greatest in the HWE in TN conditions and lowest in HWE under HS, whereas catenin α2 (Ctnna2) and desmocollin 1 (Dsc1) were highest in HWE during HS compared to all other groups. This differential expression of key genes associated with intestinal barrier integrity likely contributes to the water efficiency phenotype and the response of these birds to HS.